Geeoti: Greenhouse Terintegrasi Iot Sebagai Media Pengering Kopi yang Mampu Meningkatkan Profit Produsen Kopi Fermentasi Ayah Senaru - M. Khairul Tsani; Affansyah Arrahman; Alfan Satria Pratama; Ziadatul Fitri; Alva Riani Ulfa (International Forum of Researchers and Lecturers, 2024)
Coffee is a plantation crop that has long been planted and cultivated in Lombok. Senaru Village, Bayan District, North Lombok Regency is the largest robusta coffee producing area in Lombok with 225 hectares of coffee land. One of the coffee processing places in Senaru Village is the producer of Ayah Senaru Fermented Coffee which still uses the dry sun method with a tool called a widik. This drying method has many disadvantages because it takes a long time, is very dependent on the weather and is unhygienic. The process of drying coffee is the main factor that can determine the quality of coffee, which is why there is a need for technology as a coffee drying medium that is capable of producing quality coffee. Handling after harvest can be improved by applying modern coffee drying technology, namely greenhouses. The aim of this activity is to increase partner profits through an IoT integrated coffee drying greenhouse (GEEOTI) which is able to streamline coffee drying time and produce hygienic coffee skin waste. The method applied is the creation of GEEOTI, socialization of its use and analysis of the impact on increasing partner profits. The results of the research are that greenhouses can have a positive effect in speeding up, flattening the drying process and improving the quality of coffee compared to conventional methods. The waste from the coffee skins produced also becomes more hygienic coffee waste so it can be used as cascara tea. This activity can certainly increase partner profits by up to 100%. The partner's income, which was initially only IDR 5,100,000, was able to become IDR 13,950,000 per month because with the use of GEEOTI there was an increase in the price of coffee and the addition of a by-product in the form of cascara tea from coffee skin waste.